Evaluation of Nurses’ Performance Regarding Intravenous Cannulation - Bashar R. Mohammed Ali, Ibrahim Alwan Al-Ashour, Mohammed Hakim Shamran Al-Hchaim, Mohammed Abdualkareem Aljanabi, Jinan Fadhel Kadum (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: aimed to evaluate nurses’ performance regarding intravenous cannulation. Methodology: In order to attain the initial stated purpose, descriptive research was conducted for the current study. The research was conducted between February 20 and March 21, 2018. The research was conducted at AL-Najaf City/AL-Najaf AL-Ashraf Health Center Directorate / AL-Sader Medical City & AL-Zahra Teaching Hospital. A non-probability (accidental sample) of (100) male and female nurses working at AL-Sader Medical City and AL-Zahra Teaching Hospital with at least one year of experience. Before assigning them to the research, we received their permission. A tool for assessing the intravenous cannulation skills of nurses was used. The data were collected using the observational checklist approach of the designed questionnaire, which was observed three times using the English version of the questionnaire, and the researchers conducted interviews in the same manner. Validity of the study instrument is conducted through a panel of experts with years of experience in the nursing field. The information was analyzed using inferential statistics, which included the mean of scores, as well as descriptive statistical analysis techniques, which included frequency, percentage, and cumulative percentage. Results: According to the research, al-Sader Medical City and Al-Zahraa Teaching Hospitals in Najaf have poor or insufficient intravenous cannulation nursing abilities. In the two hospitals, it was discovered that, respectively, 94% and 82% of the nursing staff were poor. Conclusion: The research found that most nurses utilize inadequate IV cannulation techniques. The study recommendation advises nurses to join in training sessions to develop their abilities in IV cannulation. Keywords: Evaluation, Nurses’ Performance, Intravenous Cannulation.